The Physicochemical Properties of Flavor Enhancer Made from Different Types of Snail Protein Hydrolysates - Dwi Ernawati; Dedin Finatsiyatull Rosida (Food, Agriculture and Natural Resources - NETWORKS, 2022)
Golden apple snails, apple snails, and freshwater snails are mollusks found in shallow waters with mud on the bottom, such as rice fields, swamps, and riverbanks. Snail has a high protein content of 14%-19%, but its utilization is still limited. In addition, certain types of snails, such as golden apple snails and apple snails, are pests to rice plants, so they have not been used optimally. One alternative is using snail as a flavor enhancer. Flavor enhancers can be made through enzymatic hydrolysis using bromelain enzymes. This study aimed to determine the effect of snail type and hydrolysis time on the physicochemical properties of flavor enhancer made of snail protein hydrolysate. This experimental study used a completely randomized design with two factors. Factor I was the type of snail (golden apple snail, apple snail, and freshwater snail), and factor II was the hydrolysis time (3 hours, 6 hours, and 9 hours). Data were analyzed using ANOVA with α 5%. When significant difference was identified, DMRT test at 95% significance level will be conducted. The result has showed that the flavor enhancer made of snail protein hydrolysate is influenced by different snail types and hydrolysis time. The apple snail with 9-hour hydrolysis produces the best flavor enhancer characterized by 3.96% water content, 14.73% yield, 92.29% water solubility, oil absorption of 1.15 ml/g, glutamic acid content of 107.23 ppm, and brownish yellow tone.